The textual tradition of Plato's Timaeus and Critias - Jonkers, Gijsbert. (Mnemosyne, Supplements, 2017)
In The Textual Tradition of Plato's Timaeus and Critias, Gijsbert Jonkers provides new insights into the extant ancient and medieval evidence for the text of both Platonic dialogues. The discussions are set in the broader context of examinations in recent decades of the textual traditions of other individual Platonic works. Particularly the vast collection of testimonia of the Timaeus , one of Plato's most read, interpreted and discussed dialogues of all times, will be of interest for students of ancient philosophy, science and philology.